Impact of choledochotomy techniques during laparoscopic CBD exploration on short- and long-term clinical outcomes: Time to change concepts (a retrospective cohort study). (November 2020) - Ahmed, Emad Ali; Redwan, Alaa Ahmed
Abstract: Background: complications after laparoscopic common bile duct exploration (LCBDE) regarding choledochotomy techniques have not been adequately studied in the literature. Therefore, this study aimed to retrospectively analyze and compare the impact of choledochotomy techniques during LCBDE among patients with choledocholithiasis during the early and late postoperative periods. Methods: From March 2014 to February 2018, 85 patients with choledocholithiasis (52 females and 33 males) were enrolled in this study. These patients were treated by LCBDE using various choledochotomy techniques, including scalpel or scissor (28 patients, 33%) in group I, diathermy hook (35 patients, 41%) in group II, or an ultrasonic device (22 patients, 26%) in group III. Postoperative follow-up was done for assessment of all possible complications, either early (within the first six months postoperatively) or late (2–6 years postoperatively), with meticulous observation and study of any relevant postoperative events. Results: No statistical difference was detected among the three groups regarding the short- and long-term clinical outcomes, including biliary fistula, biliary stricture, cholangitis, recurrent stones, peritoneal sepsis, wound sepsis, or wound dehiscence. Conclusion: The long-lasting concepts of avoidance of using energy machines such as diathermy and ultrasonic devices with biliary structures should be changed. However, a statistical type I error cannot be excluded because of the small sample size. Therefore, further analysis of prospective randomized studies with a larger number of participants is strongly recommended. Highlights: Laparoscopic common bile duct exploration could be preferred for managing choledocholithiasis. The studied choledochotomy techniques did not affect postoperative outcomes. New versions of energy machines with precise calibration produce minimal nearby tissue damage.